Revisiting the effectiveness of repetitive transcranial magnetic stimulation treatment in depression, again. (August 2022) - Fitzgerald, Paul B; Gill, Shane; Breakspear, Michael; Kulkarni, Jayashri; Chen, Leo; Pridmore, Saxby; Purushothaman, Subramanian; Galletly, Cherrie; Clarke, Patrick; Ng, Felicity; Hussain, Salam; Chamoli, Suneel; et al.
Following on from the publication of the Royal Australian and New Zealand Journal of Psychiatry Mood Disorder Clinical Practice Guidelines (2020) and criticisms of how these aberrantly addressed repetitive transcranial magnetic stimulation treatment of depression, questions have continued to be raised in the journal about this treatment by a small group of authors, whose views we contend do not reflect the broad acceptance of this treatment nationally and internationally. In fact, the evidence supporting the use of repetitive transcranial magnetic stimulation treatment in depression is unambiguous and substantial, consisting of an extensive series of clinical trials supported by multiple meta-analyses, network meta-analysis and umbrella reviews. Importantly, the use of repetitive transcranial magnetic stimulation treatment in depression has also been subject to a series of health economic analyses. These indicate that repetitive transcranial magnetic stimulation is a cost-effective therapy and have been used in some jurisdictions, including Australia, in support of public funding. An argument has been made that offering repetitive transcranial magnetic stimulation treatment may delay potentially effective pharmacotherapy. In fact, there is considerably greater danger of the opposite happening. Repetitive transcranial magnetic stimulation is as, if not more effective, than antidepressant medication after two unsuccessful medication trials and should be a consideration for all patients under these circumstances where available. There is no meaningful ongoing debate about the use of repetitive transcranial magnetic stimulation treatment in depression – it is a safe, effective and cost-effective treatment.